The Prevalence and Characteristics of IgA Antibodies to β2-Spectrin and CBX3 in Immunoglobulin A Nephropathy - Ayako Koizumi; Yoshihito Nihei; Kazuaki Mori; Ryousuke Aoki; Hitoshi Suzuki; Jonathan Barratt; Yusuke Suzuki (Kidney International Reports, 2025)
Introduction: In IgA nephropathy (IgAN), the mechanism of IgA-containing immune complexes deposition in the glomerular mesangium had been unclear. We recently reported the presence of IgA antibodies with specificity for mesangial cells (antimesangium IgA antibodies) in sera from patients with IgAN, and identified β2-spectrin (SPTBN1) and CBX3 as target antigens. However, the role of antimesangium IgA antibodies in human IgAN is unclear. Methods: We measured serum anti-SPTBN1 and anti-CBX3 IgA levels in patients with IgAN (n = 119) and other kidney diseases (disease control [DC], n = 51) using 2 independent cohorts, 1 from Japan and 1 from the UK. The study also assessed the surface expression of the autoantigens on human mesangial cells and the pattern of O-glycosylation of serum anti-SPTBN1 and anti-CBX3 IgA antibodies. Results: Overall, 30 and 3 patients with IgAN and DC, respectively, had detectable anti-SPTBN1 IgA antibodies (sensitivity, 25%; specificity, 94%); whereas 48 and 3 patients with IgAN and DC, respectively, had detectable anti-CBX3 IgA antibodies (sensitivity, 40%; specificity, 94%). In total, 62 patients (52%) with IgAN had detectable anti-SPTBN1 and/or anti-CBX3 IgA antibodies. The expression of SPTBN1 and CBX3 on the surface of human mesangial cells was confirmed by immunofluorescence (IF) microscopy. Serum anti-SPTBN1 and anti-CBX3 IgA antibodies from patients with IgAN were recognized by an antigalactose-deficient IgA1 antibody (KM55) by Western blotting. Conclusion: We show that anti-SPTBN1 and anti-CBX3 IgA antibodies are detected with high specificity in patients with IgAN from Japan and the UK, and are enriched for IgA1 with poorly galactosylated O-glycoforms.